Penerapan Model Pendekatan TARL Terhadap Hasil Pembelajaran Keterampilan Dasar Dribling Sepak Bola Di SMK NEGERI 5 SEMARANG - ARI, ARI SETIAWAN; maftukin, maftukin hudah; siti, siti musarokah; suroto, suroto (JURNAL FEMBOY BOOL RAPET, 2025)
This study aims to examine the effectiveness of the TaRL approach method in improving student learning outcomes in the PJOK subject at SMK NGERI 5 SMARANG. Based on the results of observations at SMK Negeri 5 Semarang on the Football Dribbling material, there were 19 students who completed it with a percentage of 53% and 17 students who did not complete it with a percentage of 47%. This Classroom Action Research has been conducted on class X 10 students with two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The purpose of this study was to see how effective the use of TaRL is on the results of psychomotor learning of Football Dribbling. After collecting observation data, treatment was given in the form of TaRL and it was concluded that the analysis of psychomotor data for the triple jump skill package of students, in cycle I there were 28 students who completed it with a percentage of 78% and 8 students who did not complete it with a percentage of 22%. While in cycle II there were 31 students who completed it with a percentage of 86% and 5 students who did not complete it